Left atrial appendage closure outcomes in relation to atrial fibrillation patterns: a comprehensive analysis - Zhao, Mingzhong; Yu, Jiangtao; Hou, Cody R.; Post, Felix; Zhang, Lei; Xu, Yuhui; Herold, Nora; Walsleben, Jens (Frontiers in Cardiovascular Medicine, 2024)
Objective The effect of atrial fibrillation (AF) patterns on outcomes remains controversial. This study aims to evaluate the influence of AF type on the risk of cardiocerebrovascular events after left atrial appendage closure (LAAC) at long-term follow-up. Methods AF was categorized as paroxysmal AF (PAF) and non-PAF (NPAF). The baseline characteristics, procedural data, peri-procedural complications, and long-term outcomes between patients with PAF and NPAF after LAAC were compared. Results We analyzed 410 AF patients (mean age 74.8 ± 8.2 years; 271 male; 144 with PAF, 266 NPAF). The NPAF group tended to be older (≥75 years), male, and have chronic kidney disease (CKD) compared with the PAF group. The procedural data and peri-procedural complications were comparable. During 2.2 ± 1.5 years of follow-up, the incidences of thromboembolism, major bleeding, and device-related thrombus (DRT) did not differ between the two groups. The observed risk of thromboembolism and major bleeding was significantly lower than the estimated risk based on the CHA2DS2-VASc and HAS-BLED scores, respectively, in patients who underwent LAAC, regardless of the AF type. NPAF patients were associated with a higher risk of all-cause mortality, non-cardiovascular mortality, and combined efficacy endpoints. This association disappeared after propensity score matching (PSM) analysis. Conclusions The risk of thromboembolism and major bleeding was lower in patients who underwent LAAC, regardless of the AF type. Although NPAF often coexists with multiple risk factors, it was not associated with worse long-term outcomes after LAAC when compared with PAF.